Magnetic Simulation and Analysis of Radial Flux Permanent Magnet Generator using Finite Element Method - Irasari, Pudji; Alam, Hilman Syaeful; Kasim, Muhammad (Research Centre for Electrical Power and Mechatronics, Indonesian Istitutes of Sciences, 2012)
This paper discusses magnetic simulation and analysis of radial flux permanent magnet generator (PMG) using finite element method (FEM) by utilizing open source software FEMM 4.2. The specification of generator is 25 V, 28 A, 3 phase, 300 rpm. The analyzed magnetic flux was in the air gap, stator teeth and slots to find out the distribusian pattern and its fluctuation. The simulations were conducted in no-load and nominal load (28 A) conditions. Furthermore the maximum flux density of simulation (Bg(sim)) was used to calculate phase voltage Eph to find out the magnitude of generated electromotive force (EMF). The calculation results were presented as voltage vs. rotation graph in no-load condition and voltage vs. current graph in nominal load condition. Both graphs were validated with Eph of experiment result (Eph(exp)) and Eph that the value of Bg obtained from analytical calculation (Eph(calc)). The final results showed that in no-load condition, Eph graph with Bg(sim) (Eph(sim)) was close to Eph(exp) and Eph(calc). The error rate with respect to the experiment was 6,9%. In nominal load condition, Eph(sim) graph almost coincides with Eph(calc.) graph, with the voltage drop of both was 0,441 V. Both graphs however were far different from Eph(exp) graph, which has 9 V of voltage drop. The overall results demonstrated that magnetic distribution pattern presented by FEM was very helpful to avoid magnetic flux accumulation in a particular segment. Besides Bg(sim) facilitated to predict the value of Eph.